2011
DOI: 10.1186/cc10483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supraglottic airway versus endotracheal intubation for the pre-hospital treatment of out-of-hospital cardiac arrest

Abstract: IntroductionBoth supraglottic airway devices (SGA) and endotracheal intubation (ETI) have been used by emergency life-saving technicians (ELST) in Japan to treat out-of-hospital cardiac arrests (OHCAs). Despite traditional emphasis on airway management during cardiac arrest, its impact on survival from OHCA and time dependent effectiveness remains unclear.MethodsAll adults with witnessed, non-traumatic OHCA, from 1 January 2005 to 31 December 2008, treated by the emergency medical services (EMS) with an advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 22 publications
2
85
0
5
Order By: Relevance
“…50,54,[56][57][58]61 Several retrospective observational studies show more favorable outcome with the use of an SGA device, whereas other studies favor the use of endotracheal intubation. 47,49,50,[59][60][61] 2015 Recommendations-Updated Either a bag-mask device or an advanced airway may be used for oxygenation and ventilation during CPR in both the inhospital and out-of-hospital setting (Class IIb, LOE C-LD).…”
mentioning
confidence: 99%
“…50,54,[56][57][58]61 Several retrospective observational studies show more favorable outcome with the use of an SGA device, whereas other studies favor the use of endotracheal intubation. 47,49,50,[59][60][61] 2015 Recommendations-Updated Either a bag-mask device or an advanced airway may be used for oxygenation and ventilation during CPR in both the inhospital and out-of-hospital setting (Class IIb, LOE C-LD).…”
mentioning
confidence: 99%
“…Recently, some studies suggested that earlier epinephrine administration and earlier endotracheal intubation contributed to improving outcomes after OHCA. 25,26 Further elaborate studies that consider the timing of the procedure or the patient's rhythm are needed to confirm the effect of ALS measures.…”
Section: Kitamura Et Al Improvements In Ohca Survival In Japan 2837mentioning
confidence: 99%
“…Zu diesem Thema existieren mehrere große retrospektive Studien [24][25][26][27][28]. Problematisch bei der Beurteilung der Relevanz dieser zahlenmäßig enorm großen Studien sind die unterschiedlichen Einschlusskriterien und insbesondere die unterschiedlichen Rettungsdienstsysteme.…”
Section: Die Optimale Beatmungsformunclassified